1994
DOI: 10.1002/1097-0142(19941101)74:9<2425::aid-cncr2820740906>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Impact of age and sex on survival after curative resection for carcinoma of the esophagus

Abstract: Background. The impact of age and sex‐related changes in the endogenous hormonal milieu on survival after curative resection for esophageal epithelial cancer is explored. Adami et al. have suggested that the event of puberty has a favorable impact on survival after treatment of epithelial cancers. Methods. The database consisted of 469 patients with esophageal cancer treated surgically with an intent to cure (without any gross residual disease at the end of the primary treatment) at Tata Memorial Hospital betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…Esophageal cancer is highly lethal with 11,650 (88.7%) estimated deaths among men and 2,850 (81.2%) among women. 2 Taken together with previous population studies, [3][4][5][6][7][8][9] the latter suggests a survival benefit for women when compared with men. The prevalence of the two main histologic subtypes-adenocarcinoma and squamous cell carcinoma-differs depending on geographic location.…”
Section: Introductionmentioning
confidence: 98%
“…Esophageal cancer is highly lethal with 11,650 (88.7%) estimated deaths among men and 2,850 (81.2%) among women. 2 Taken together with previous population studies, [3][4][5][6][7][8][9] the latter suggests a survival benefit for women when compared with men. The prevalence of the two main histologic subtypes-adenocarcinoma and squamous cell carcinoma-differs depending on geographic location.…”
Section: Introductionmentioning
confidence: 98%
“…The gender of the patient was found to be the second most significant determinant of survival (p = 0.002) after lymph node metastasis. These results of better survival benefit for women provides support for the hypothesis that the endocrine milieu in premenopausal women may prevent the micrometastases of the oesophageal malignancy and the consequent improved prognosis for oesophageal cancer [26]. …”
Section: Introductionmentioning
confidence: 76%
“…Badwe et al (1994) studied the impact of age and sex on survival after curative resection for carcinoma of the oesophagus with life stable analysis showing a significantly better 5 year survival for women under 49 years of age (35%, CI 24-48) compared with men of the same age (16%.CI 8-27) (P < 0.008)[26]. The gender of the patient was found to be the second most significant determinant of survival (p = 0.002) after lymph node metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…Wichmann et al [17] reported that women with colorectal cancer had more favorable outcomes than men. Badwe et al [18] reported that young women with esophageal cancer showed a survival advantage. Furthermore, other reports have shown that long-term survival after surgical resection of the esophagus is better in women than in men [9,19].…”
Section: Discussionmentioning
confidence: 99%